1997
DOI: 10.1006/dbio.1997.8617
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Transcription Factor AP-2: Cloning, Expression and Its Role in Outgrowth of Facial Prominences and Limb Buds

Abstract: Embryonic facial development in chick embryos involves a sequential activation of genes that control differential growth and patterning of the beak. In the present study we isolate one such gene, the transcription factor, AP-2, that is known to be expressed in the face of mouse embryos. The protein sequence of chick AP-2alpha is 94% homologous to human and mouse AP-2. Wholemount in situ hybridization with a probe for chick AP-2 identifies expression from primitive streak stages up to stage 28. The most strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 70 publications
12
92
0
3
Order By: Relevance
“…Although an in vivo role for Stats downstream of FGFR2 has not yet been shown, mouse models of craniosynostosis containing altered FGFR2, display several phenotypes that overlap with those observed in FKO, Wnt1-Cre; Floxdel/KI, or Tcfap2a ϩ/Ϫ mice including shortened snouts, dental malocclusion, widespaced eyes, and cleft palate (Zhang et al, 1996;Nottoli et al, 1998;De Moerlooze et al, 2000;Hajihosseini et al, 2001;Eswarakumar et al, 2002Eswarakumar et al, , 2004Chen et al, 2003;Brewer et al, 2004;Nelson and Williams, 2004;Wang et al, 2005). Thus, the presence of a STAT site in the FNP/LBM-specific enhancer likely places AP-2␣ downstream of FGFR signaling in the FNP, which is consistent with other studies showing FGF-dependent changes of Tcfap2a in the craniofacial region (Shen et al, 1997;Cordero et al, 2004).…”
Section: Stat Proteins Act Upstream Of Tcfap2amentioning
confidence: 53%
See 2 more Smart Citations
“…Although an in vivo role for Stats downstream of FGFR2 has not yet been shown, mouse models of craniosynostosis containing altered FGFR2, display several phenotypes that overlap with those observed in FKO, Wnt1-Cre; Floxdel/KI, or Tcfap2a ϩ/Ϫ mice including shortened snouts, dental malocclusion, widespaced eyes, and cleft palate (Zhang et al, 1996;Nottoli et al, 1998;De Moerlooze et al, 2000;Hajihosseini et al, 2001;Eswarakumar et al, 2002Eswarakumar et al, , 2004Chen et al, 2003;Brewer et al, 2004;Nelson and Williams, 2004;Wang et al, 2005). Thus, the presence of a STAT site in the FNP/LBM-specific enhancer likely places AP-2␣ downstream of FGFR signaling in the FNP, which is consistent with other studies showing FGF-dependent changes of Tcfap2a in the craniofacial region (Shen et al, 1997;Cordero et al, 2004).…”
Section: Stat Proteins Act Upstream Of Tcfap2amentioning
confidence: 53%
“…Relative intensity and domain of expression is indicated by (ϩ), while (Ϫ) indicates that no expression was observed in the transgenic embryos. The notation "nr" indicates that the number of transgenic embryos that failed to give specific staining was not recorded, but was greater than 2. mouse and chick face (Mitchell et al, 1991;Shen et al, 1997), the analysis was initiated using whole cell protein extracts derived from the chick FNP mesenchyme. Differences in the mechanisms of embryogenesis between mouse and chick, particularly the contrast between in utero versus in ovo development, make the chick a more efficient and cost-effective system for an initial analysis of the DNA binding proteins present in the early face.…”
Section: Sox Factors Bind the Dce In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Expression analyses in mammals, birds, and amphibians showed that AP-2 genes are involved in the formation of craniofacial, neuroectodermal, ectodermal structures, limb buds, and urogenital tissues (Mitchell et al, 1991;Snape et al, 1991;Moser et al, 1995Moser et al, , 1997aShen et al, 1997;Epperlein et al, 2000). The functional relevance of AP-2 proteins for mammalian development was demonstrated by the lethal phenotypes of AP-2␣, AP-2␤, and AP-2␥ mouse mutants.…”
Section: Introductionmentioning
confidence: 99%
“…To perturb the spatiotemporal pattern of retinoid signaling in the limb, beads (AG1-X2, formate form, Bio-Rad) were soaked in 5 mg/ml all trans-retinoic acid (Sigma) dissolved in dimethylsulfoxide and rinsed in DMEM (Gibco) plus 10% fetal calf serum (Gibco) as described in Shen et al (1997). Two or three beads, each approximately 100 m in diameter, were implanted into the proximal limb bud near the prospective crural or sciatic plexus region of St. 21.5-22.5 embryos, as illustrated in Figure 4A.…”
Section: Retinoic Acid Treatmentmentioning
confidence: 99%